Hydrogen sorption, kinetics, reversibility, and reaction mechanisms of MgH2-xLiBH4 doped with activated carbon nanofibers for reversible hydrogen storage based laboratory powder and tank scales. (28th September 2017) - Thaweelap, Natthaporn; Thongtan, Puttimate; Sitthiwet, Chongsutthamani; Thiangviriya, Sophida; Eiamlamai, Priew; Utke, Rapee
Abstract: De/rehydrogenation kinetics and reversibility of MgH2 are improved by doping with activated carbon nanofibers (ACNF) and compositing with LiBH4 . Via doping with 5 wt % ACNF, hydrogen absorption of Mg to MgH2 ( T = 320 °C and p (H2 ) = 50 bar) increases from 0.3 to 4.5 wt % H2 . Significant reduction of onset dehydrogenation temperature of MgH2 to 340 °C (Δ T = 70 °C as compared with pristine MgH2 ) together with 6.8–8.2 wt % H2 can be obtained by compositing Mg-5 wt. % ACNF with LiBH4 (LiBH4 :Mg mole ratios of 0.5:1, 1:1, and 2:1). During dehydrogenation of Mg-rich composites (0.5:1 and 1:1 mol ratios), the formation of MgB2 and Mg0.816 Li0.184 implying the reaction between LiBH4 and MgH2 favors kinetic properties and reversibility, while the composite with 2:1 mol ratio shows individual dehydrogenation of LiBH4 and MgH2 . For up-scaling to hydrogen storage tank (∼120 times greater sample weight than laboratory scale) of the most suitable composite (1:1 mol ratio), de/rehydrogenation kinetics and hydrogen content released at all positions of the tank are comparable and approach to those from laboratory scale. Due to high purity (100%) and temperature of hydrogen gas from hydride tank, the performance of single proton exchange membrane fuel cell enhances up to 30% with respect to the results from compressed gas tank. Highlights: Effects of ACNF doping contents and LiBH4 :Mg mole ratios on kinetics of MgH2 . Increasing H2 absorption of MgH2 from 0.3 to 4.5 wt % by doping with 5 wt % ACNF. Different reaction mechanisms by altering LiBH4 :Mg mole ratios. Homogeneous H2 absorption and desorption at all positions in H2 storage tank. Up to 30 % increment of single PEMFC performance by using H2 from hydride tank.